Investigating the damage from the February 6, 2023 earthquakes in terms of building characteristics in the Antakya and Defne districts of Hatay province - Sakarya, Adem; Akin, Oya; Kilic, Ali (ELSEVIER, 2024)
On February 6, 2023, T & uuml;rkiye experienced two major earthquakes centered in Kahramanmara & scedil; and felt in 11 provinces. As a result, more than 50,000 people were killed and more than 100,000 buildings collapsed or were heavily damaged. This great destruction shows again the importance of cities being resilient against disasters. This study examines earthquake damage to buildings in terms of settlement suitability and building characteristics in densely built areas of Antakya and Defne, the central districts of Hatay province where the building damage rate was the highest. The study has identified two main questions regarding whether the suitability of the ground for settlement can be differentiated in terms of earthquake damage and whether building characteristics affect earthquake damage in terms of the different suitability categories. Suitability is analyzed under three categories: critically suitable, moderately suitable, and suitable. Building characteristics involve building height, ground coverage area, number of basement floors, and total construction area. The study uses geographic information systems to determine settlement suitability and superimpose this over damage. Additionally, multinomial logistic regression is used to analyze the effect of building characteristics on earthquake damage, with the results showing earthquake damage to be higher in critically and moderately suitable areas. In terms of building characteristics, building height has the greatest effect on earthquake damage, while the presence of a basement floor reduces earthquake damage, especially in critically suitable areas. An increase in the ratio of building height to ground coverage area was also found to be a factor that increases earthquake damage.
Keywords: Resilience; Damage assessment; Earthquake; Urban planning; Hatay; MULTINOMIAL LOGISTIC-REGRESSION; SOIL-STRUCTURE INTERACTION; Geology; Meteorology & Atmospheric Sciences; Water Resources